Analiza wskaźnikowa jako narzędzie oceny sytuacji finansowej na przykładzie PKN Orlen SA - Wiatrzyk, Krzysztof (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
This article presents the essence and importance of one of the components of the financial analysis, i.e. an index analysis based on the example of PKN Orlen SA. In the current economic system associated with competitiveness, where the availability of quantitative data increases significantly, the use of ratio analysis is the basic and widely used tool for assessing the financial condition of operations. The aim of the article is to show the most important indicators of the ratio analysis, enabling the assessment of the entity’s activity using financial reporting on the one hand and taking into account market trends on the other. The ratio analysis enables comparability of financial data both in the current and next period. Nevertheless, while practicing it, one should remember to follow the basic rules dictated by financial analysis.
Keywords: debt ratio; index; unit; PKN Orlen SA; financial condition; profitability indicator; turnover ratio; liquidity ratio; ratio analysis